Consumer preferences for water supply? An application of choice models to urban India - P. B. Anand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper examines consumer preferences for the attributes of alternative sources of water supply in Chennai, based on a household survey where respondents were given the description of a set of options. Their decision to choose one of the options is examined using discrete choice models. Whether consumer preferences are hierarchical or lexicographic is also briefly examined. Access to a yard tap is considered to be a more important attribute than water quantity, quality and the provider (the private sector or public sector). In general, the estimated willingness to pay is substantially higher than the present monthly water expenditures. However, some consumers, specially those living in the peri-urban areas, do not seem to be willing to pay for water supply improvements. Among the plausible reasons are a lack of trust in the public utility or a manifestation of the equity politics in India (the peri-urban households claiming their entitlement to subsidized water), or the presence of preference reversal.
Keywords: C25; D12; L95; Q25; R22; 330; water supply; consumer preferences; discrete choice; lexicographic preferences; Wasserversorgung; Konsumentenverhalten; Präferenztheorie; Theorie; Stadt; Indien